The motivations for the diversification of the Nigerian economy focusing on sustainable agriculture - Neszmélyi , György Iván (Applied Studies in Agribusiness and Commerce, 2014)
Agriculture is one of the major branches of the economy in Nigeria, the most populous country in Africa. It employs around 70% of the population and its contribution to the national GDP ranges around 45% (2012). In spite of the fact that most of the area is arable the majority of food, the Nigerian population consumes, comes from imports. The paper attempts to provide in insight to the reasons, why Nigeria could still not achievew self sufficiency from major food crops and livestock. Beyond the rapid growth of the population, one of the major reasons is the rich oil and natural gas reserves, the exploitation and export of which has been providing with the country with “easy cash” for the recent few decades. Another reason is that the agricultural holdings are small and scattered, and farming is carried out with simple tools and techniques. Modern and large-scale farms are not common. The political leadership and economic decision makers of the country already recognized the necessity of the development of the food and agricultural sector, which – contrary to the oil industry – would exercise a deep and positive impact on the rural society as well. Nigerian agriculture is being transformed towards commercialization at small, medium and large-scale enterprise levels.